2021
DOI: 10.3390/ijerph18041590
|View full text |Cite
|
Sign up to set email alerts
|

A Successful Pilot Experiment of Salt Reduction in Tunisian Bread: 35% Gradual Decrease of Salt Content without Detection by Consumers

Abstract: As bread is the most consumed food by the Tunisian population and the major source of salt, a pilot experiment of salt reduction in bread was begun in Bizerte city. Salt analysis in bread collected from Bizerte city was done with the Volhard titration method. A one-way Anova test was carried out to assess salt content changes over time. Application of the salt reduction programme allowed a gradual decrease of salt content in bread by 35% during three years without detection by Tunisian consumers. The salt conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The results showed that for white bread, average salt levels decreased from 17.8 g/kg in 2011 to 13.1 g/kg in 2016 (more than 25% reduction), while highlighting large discrepancies between different bakeries, with a range of 10.5 to 19.6 g/kg [ 192 ]. In Tunisia, and more specifically, in Bizerte city, where the pilot phase of the national action plan is implemented, bread samples were collected randomly from bakeries once per week during the first three months and then, once every three months during the next period of the protocol, which extended between 2015 and 2018 [ 182 ]. Salt levels in bread was estimated at 1.7 g/100 g in 2015, and this level reached 1.1 g/100 g in 2018, i.e., after 3 years of implementing the salt reduction program.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that for white bread, average salt levels decreased from 17.8 g/kg in 2011 to 13.1 g/kg in 2016 (more than 25% reduction), while highlighting large discrepancies between different bakeries, with a range of 10.5 to 19.6 g/kg [ 192 ]. In Tunisia, and more specifically, in Bizerte city, where the pilot phase of the national action plan is implemented, bread samples were collected randomly from bakeries once per week during the first three months and then, once every three months during the next period of the protocol, which extended between 2015 and 2018 [ 182 ]. Salt levels in bread was estimated at 1.7 g/100 g in 2015, and this level reached 1.1 g/100 g in 2018, i.e., after 3 years of implementing the salt reduction program.…”
Section: Resultsmentioning
confidence: 99%
“…Salt levels in bread was estimated at 1.7 g/100 g in 2015, and this level reached 1.1 g/100 g in 2018, i.e., after 3 years of implementing the salt reduction program. Hence, the average salt reduction was of 35% in bread [ 182 ]. In parallel, a pilot study on consumer acceptability of the salt-reduced bread was conducted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the salt dose is to be reduced, even partially, it must be reduced gradually. As an example, a 35% salt content reduction (from 1.7% to 1.1%) was achieved during three years without consumer detection [ 99 ]. In case of a rapid decrease, it is possible to use salt substitutes or flavour enhancers; in industrial production it is mainly potassium chloride.…”
Section: Salt Content Reduction and Its Consequencesmentioning
confidence: 99%
“…The sodium chloride reduction up to 25% in six weeks or even up to 52% in four weeks did not affect the consumer's acceptability or bakery products consumption. However, if the reduction of salt in food is done too quickly without necessary adjustments in food taste, the opposite effect can be reached, namely it can lead consumers to other foods rich in salt or to add it during the preparation of meals or to supplement the lack of salt in that food [51,[80][81][82] Inhomogeneous distribution of salt in the bread recipe May lead to a reduction up to 20-30% NaCl content from the bakery products with good results from the sensory point of view but may presents negative effects on yeast activity [83][84][85][86] Table 2. Cont.…”
Section: Strategies Effects Referencesmentioning
confidence: 99%